Anti-Allergic Activity of Methanolic Extract of Lagenaria Siceraria Mol. Standley Leaves - Jasani, Nidhi; Tripathi, Nagja; Kumar, Vimal (Indian Journal of Natural Products, 2019)
Background: Lagenaria siceraria Mol. Standley commonly known as bottle gourd is a climbing perennial herb cultivated as a vegetable in the tropical countries. Lagenaria siceraria leaves are used traditionally for cough, bronchitis, asthma and inflammation. Purpose: On basis of ethano-medicinal uses, the anti-allergic activities of the methanolic extract of Lagenaria siceraria leaves was planned to investigate scientifically using animal models for allergic inflammation and anti-allergic activity. Method: Leaves of Lagenaria siceraria were collected from Nirma Herbal Wealth, Nirma University, Ahmedabad, Gujarat, India and the sample was identified and authenticated by ethano- botanist. The methanolic extract of the leaves was prepared from 500 gm of leaves using soxhlet extraction; it yielded 16.70 % (w/w) of dry extract. The Wistar rats were killed by exsanguinations. The pieces of mesenteries were spread and challenged with 1µg/ml of compound 48/80 for 10 min as negative control. Methanolic extract L. siceraria at different concentrations or standard ketotifen incubated mesenteries were challenged with 1µg/ml of compound 48/80 for 10 min. Pieces of mesentery were stained with 0.1% toludine blue solution and the % of degranulated mast cells were counted under microscope and the protection offered by methanolic extract / ketotifen of was calculated. In another model the Compound 48/80 (0.3μg in 0.05ml) were administered subcutaneously in the plantar region of the right hind paw of albino mice's.Result: The methanolic extract of L. siceraria (LSM) showed significant dose dependent (10-30 µg/ml) anti allergic activity against compound 48/80 induced mast cell degranulation in rat mesenteries. LSM also showed significant anti-inflammatory effects at the dose of 100 mg/kg against compound 48/80 induced paw edema in mice. Conclusion: The ethno medicinal uses of L. siceraria leaves were proved by us scientifically for treatment of allergic inflammation and anti-allergic activity using various animal models.
Keywords: Lagenaria siceraria; mast cell stabilization; compound 48/80; paw edema